Viral Infection in Renal Transplant Recipients - Jovana Cukuranovic; Sladjana Ugrenovic; Ivan Jovanovic; Milan Visnjic; Vladisav Stefanovic (The Scientific World Journal)
Viruses are among the most common causes of opportunistic infection after transplantation. The risk for viral infection is a function of the specific virus encountered, the intensity of immune suppression used to prevent graft rejection, and other host factors governing susceptibility. Although cytomegalovirus is the most common opportunistic pathogen seen in transplant recipients, numerous other viruses have also affected outcomes. In some cases, preventive measures such as pretransplant screening, prophylactic antiviral therapy, or posttransplant viral monitoring may limit the impact of these infections. Recent advances in laboratory monitoring and antiviral therapy have improved outcomes. Studies of viral latency, reactivation, and the cellular effects of viral infection will provide clues for future strategies in prevention and treatment of viral infections. This paper will summarize the major viral infections seen following transplant and discuss strategies for prevention and management of these potential pathogens.